Phonological development in a bilingual child - Avendaño, Abelardo (Lenguas Modernas, 2017)
This paper examines one aspect of linguistic competence, i.e., phonological ability, and reports on the course of the phonological development of a sixyear- old Spanish-English primary bilingual child. Primary bilinguals (those simultaneously acquiring two languages before about age six) seem to achieve monolingual-like pronunciation in both of their languages, at least as f'ar as a phonetically trained listener canjudge. In order to explore such dual oral performance, fragments of spontaneous, informal conversation in Spanish (Chilean Spanish) and in English (General American English) are analysed and discussed in some detail. Some theoretical aspects underpinning phonological processing and bilingual phonology are also touched upon.